STIGMA AND ITS EFFECTS ON PROPERTY MARKETABILITY: A SYSTEMATIC LITERATURE REVIEW - Nurul Liyana Ibrahim; Nurul Hana Adi Maimun (International Journal of Accounting, Finance and Business, 2022)
Stigmatized property is a global issue which has gained continuous attention since the 1990s. This type of property has generally generates a negative perception from the public and the stigma may causes a property market price to fluctuate from time to time. Every real estate agents or negotiators will have the possibility to involve in property listings involving stigmatized property and they may also face some difficulties in marketing them. Hence, this paper has carried out a systematic review on the types of stigma and the effects of stigmatized properties. The aim of this paper is to analyse the existing literature on marketability issues towards stigmatized properties. This paper performed a systematic literature search guided by the PRISMA Statement review method. Reviews from the relevant databases have resulted into three (3) main themes which are physical, non-physical, and psychological stigma, and have further produced a total of seven (7) sub-themes. It has been discussed that stigma may occur and the effect towards the property value is depended on the focus, belief, and culture of that certain location. Understanding the effects of the stigma may assist the agents involved in the stigmatized market and also guide the owners of stigmatized property in the preparation of marketing those types of properties.